Estimation of leaf area of oilseed flax (Linum usitatissimum L.) (Semiárida, 2020)
The leaf area of field-grown oil flax (Linum usitatissimum L.) was estimated during its grown-vegetative and reproductive development-by means or several indirect methods. Leaf area positively and significantly (P